2016
DOI: 10.1039/c6ob00560h
|View full text |Cite
|
Sign up to set email alerts
|

Selective inhibition of p97 by chlorinated analogues of dehydrocurvularin

Abstract: The ATPase p97 is a ubiquitin targeted segregase that uses the energy of ATP binding and hydrolysis to extract ubiquitylated substrates from biological membranes, from other proteins, or from protein complexes to carry out myriad tasks in eukaryotes. Increased p97 activity has been linked to a poor prognosis in cancer patients, making p97 an anti-neoplastic target. In the present study, we show that dehydrocurvularin (DHC) and its chlorinated variants are covalent inhibitors of p97, interfering with its ATPase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 21 publications
0
15
0
2
Order By: Relevance
“…In addition to the molecules identified by high-throughput screening, the natural products withaferin A and dehydrocurvularin have been shown to inhibit the enzyme [ 176 , 177 ].…”
Section: Therapeutic Potential Of P97 Inhibitorsmentioning
confidence: 99%
“…In addition to the molecules identified by high-throughput screening, the natural products withaferin A and dehydrocurvularin have been shown to inhibit the enzyme [ 176 , 177 ].…”
Section: Therapeutic Potential Of P97 Inhibitorsmentioning
confidence: 99%
“…Curvularins are resorcylic acid lactones of considerable biological interest because of their cytotoxic, 9 phytotoxic, 10 antimicrobial, 7b nematicidal, 11 antimycobacterial, 12 and antitrypanosomal 13 activities, their ability to act as spindle poisons, 14 and their role as inhibitors of cell division, 15 microtubule assembly, 16 and components of the ubiquitin proteasome system including the ATPase p97 and the proteasome. 17 Occurrence of altertoxins, epoxyperylenes, and perylenequinones with anti-HIV, 18 anti-leishmanial, 19 antimalarial, 19 and cytotoxic 19 activities has been recently documented in endophytic Alternaria sp. It is noteworthy that the fungal metabolite thioperylenol ( 5 ), structurally related to alterperylenepoxide A ( 4 ) and bearing a 2-hydroxy-3-mercaptopropionic acid moiety at C-6, has been converted into hydroperylene derivatives with therapeutic applications for platelet aggregation.…”
mentioning
confidence: 99%
“…Recently, cytotoxicity of compounds 6 – 8 against a small panel of human tumor cell lines has been observed, and this was partially linked to their suppressive effect on the activation of the TNFα-induced NF-κB pathway [ 28 ]. It was also reported that 8 acts as a covalent inhibitor of p97, interfering with its ATPase activity [ 29 ]. Furthermore, the antibacterial activity inhibiting the growth of E. coli of 11-hydroxylcurvularin ( 4 – 5 ) was also demonstrated [ 30 ].…”
Section: Resultsmentioning
confidence: 99%